Ambipolar, low-voltage and low-hysteresis PbSe nanowire field-effect transistors by electrolyte gating - Lokteva, Irina; Thiemann, Stefan; Gannott, Florentina; Zaumseil, Jana (Nanoscale, 2013)
Semiconductor nanowire field-effect transistors (FETs) are interesting for fundamental studies of charge transport as well as possible applications in electronics. Here, we report low-voltage, low-hysteresis and ambipolar PbSe nanowire FETs using electrolyte-gating with ionic liquids and ion gels. We obtain balanced hole and electron mobilities at gate voltages below 1 V. Due to the large effective capacitance of the ionic liquids and thus high charge carrier densities electrolyte-gated nanowire FETs are much less affected by external doping and traps than nanowire FETs with traditional dielectrics such as SiO2. The observed current–voltage characteristics and on/off ratios indicate almost completely transparent Schottky barriers and efficient ambipolar charge injection into a low band gap one-dimensional semiconductor. Finally, we explore the possibility of applying these ambipolar nanowire FETs in complementary inverters for printed electronics.
EAM Import::2019-03-13

Breakdown of Far-Field Raman Selection Rules by Light-Plasmon Coupling Demonstrated by Tip-Enhanced Raman Scattering - Poliani, Emanuele; Wagner, Markus R.; Vierck, Asmus; Herziger, Felix; Nenstiel, Christian; Gannott, Florentina; Schweiger, Manuel; Fritze, Stephanie; Dadgar, Armin; Zaumsei, Jana; Krost, Alois; Hoffmann, Axel; et al. (Journal of Physical Chemistry Letters, 2017)
We present an experimental study on the near-field light-matter interaction by tip-enhanced Raman scattering (TERS) with polarized light in three different materials: germanium-doped gallium nitride (GaN), graphene, and carbon nanotubes. We investigate the dependence of the TERS signal on the incoming light polarization and on the sample carrier concentration, as well as the Raman selection rules in the near-field. We explain the experimental data with a tentative quantum mechanical interpretation, which takes into account the role of plasmon polaritons, and the associated evanescent field. The driving force for the breakdown of the classical Raman selection rules in TERS is caused by photon tunneling through the perturbation of the evanescent field, with the consequent polariton annihilation. Predictions based on this quantum mechanical approach are in good agreement with the experimental data, which are shown to be independent of incoming light polarization, leading to new Raman selection rules for TERS.
CRIS-Team Scopus Importer:2022-04-14

Controlling the diameter of aligned single-walled carbon nanotubes on quartz via catalyst reduction time - Schweiger, Manuel; Schaudig, Maximilian; Gannott, Florentina; Killian, Manuela; Bitzek, Erik; Schmuki, Patrik; Zaumseil, Jana (Carbon, 2015)
One of the main objectives of chemical vapor deposition (CVD) growth of single-walled carbon nanotubes (SWCNT) is control over their diameter and type (metallic or semiconducting). Here, we investigate the evolution of iron catalyst particles on quartz substrates depending on the duration of the reduction step with hydrogen and its effect on the growth of horizontally aligned SWCNT. We find a strong dependence of catalyst particle size and size distribution on the initial iron film thickness and the reduction time at 630 °C. Initial decrease of the particle size is followed by an unexpected increase. Statistical analysis of the Raman radial breathing modes of the SWCNT over large areas gave reliable and reproducible diameter distributions that correlated directly with the catalyst particle size distributions. By changing the reduction time it was possible to reproducibly shift the average SWCNT diameter from 1.5 (±0.3) nm to 1.2 (±0.2) nm while maintaining a nanotube density of 5–6 SWCNT/ extgreekmm. In order to describe the evolution of the particle size during the reduction process at this particular temperature, we propose a model that includes the diffusion of iron into the quartz and its re-emergence.
WW1::1053
Keywords: Simulation and Modeling

Enhanced Ambipolar Charge Injection with Semiconducting Polymer/Carbon Nanotube Thin Films for Light-Emitting Transistors - Gwinner, Michael C.; Jakubka, Florian; Gannott, Florentina; Sirringhaus, Henning; Zaumseil, Jana (ACS nano, 2012)
We investigate the influence of small amounts of semiconducting single-walled carbon nanotubes (SWNTs) dispersed in polyfluorenes such as poly(9,9-di-n-octylfluorene-alt-benzothiadiazole (F8BT) and poly(9,9-dioctylfluorene) (F8) on device characteristics of bottom contact/top gate ambipolar light-emitting field-effect transistors (LEFETs) based on these conjugated polymers. We find that the presence of SWNTs within the semiconducting layer at concentrations below the percolation limit significantly increases both hole and electron injection, even for a large band gap semiconductor like F8, without leading to significant luminescence quenching of the conjugated polymer. As a result of the reduced contact resistance and lower threshold voltages, larger ambipolar currents and thus brighter light emission are observed. We examine possible mechanisms of this effect such as energy level alignment, reduced bulk resistance above the contacts, and field-enhanced injection at the nanotube tips. The observed ambipolar injection improvement is applicable to most conjugated polymers in staggered transistor configurations or similar organic electronic devices where injection barriers are an issue.
EAM Import::2019-03-14

Epitaxial Growth of PbSe Quantum Dots on MoS2 Nanosheets and their Near-Infrared Photoresponse - Schornbaum, Julia; Winter, Benjamin; Schießl, Stefan; Gannott, Florentina; Katsukis, Georgios; Guldi, Dirk Michael; Spiecker, Erdmann; Zaumseil, Jana (Advanced Functional Materials, 2014)
A facile one-pot synthesis of hybrid materials consisting of PbSe quantum dots (QDs) that grow epitaxially on MoS2 nanoflakes resulting in three equivalent orientation variants of the PbSe QDs with respect to the MoS2 lattice is demonstrated. The epitaxial growth and cross-sectional high-resolution transmission electron microscopy (HRTEM) investigations verify a direct and linker-free contact between the quantum dots and the transition metal dichalcogenide (TMD) nanoflakes, while maintaining surface passivation of the PbSe with oleic acid ligands on the outside. Solution-processed photodetectors based on PbSe-MoS2 hybrids exhibit stable photoconduction when illuminated with near-IR light (wavelength > 1200 nm) without any laborious ligand-exchange steps. Flexible devices fabricated on polyethylene terephthalate (PET) substrates show excellent stability upon repeated bending. These hybrid materials are air-stable and solution-processable at low temperatures and thus promising for low-cost flexible near-IR photodetectors.

Generalized enhancement of charge injection in bottom contact/top gate polymer field-effect transistors with single-walled carbon nanotubes - Wang, Ming; Jakubka, Florian; Gannott, Florentina; Schweiger, Manuel; Zaumseil, Jana (Organic Electronics, 2014)
We investigate the influence of small amounts of dispersed single-walled carbon nanotubes (SWNTs) on the contact resistance and device characteristics of bottom contact/top gate polymer field-effect transistors (FETs). Five conjugated polymers representing different classes of polymer semiconductors with different HOMO/LUMO levels are employed, namely, polythiophenes (P3HT), polyphenylenevinylenes (MDMO-PPV), polyfluorenes (F8T2), naphthalene-bis(dicarboximide) bithiophene copolymers (P(NDI2OD-T2)), and diketopyrrolo-pyrrole-bithiophene copolymers (DPPT-TT). In all cases the presence of dispersed SWNTs reduces non-ohmic contact resistance and lowers threshold and onset voltages for charge transport. In some cases inherent ambipolar charge transport in conjugated polymers (F8T2 and P(NDI2OD-T2)) is revealed. The concentration of the SWNTs within the semiconducting layer remains below the percolation limit and thus the apparent mobilities and on/off ratios are still determined by the polymer and independent of the specific type of the carbon nanotubes (metallic or semiconducting). The degree of enhancement depends both on the energy level offset between the injecting gold electrode and the HOMO/LUMO level (i.e., Schottky barrier) and the charge carrier mobility of the respective polymer. The simplicity of this injection enhancement method and its broad applicability make it a step toward high performance polymer transistors without injection limitations.
EAM Import::2019-03-13

In Situ Raman Mapping of Charge Carrier Distribution in Electrolyte-Gated Carbon Nanotube Network Field-Effect Transistors - Zaumseil, Jana; Jakubka, Florian; Wang, Ming; Gannott, Florentina (Journal of Physical Chemistry C, 2013)
Solution-processed networks of purely semiconducting single-walled carbon nanotubes (s-SWNTs) can be used to create high-mobility field-effect transistors (FETs) for flexible electronics. In order to optimize network alignment and density, an understanding of carrier distribution within the FET channel is necessary. Here, we used confocal Raman microscopy to investigate charge accumulation and doping in electrolyte-gated FETs with asymmetric layers of only (7,5) nanotubes, that were selected by dispersion in poly(9,9-dioctylfluorene). The nanotube FETs exhibited hole mobilities of up to 7.5 cm2 V–1 s–1 and on/off ratios of 105. All Raman modes decreased in intensity with hole accumulation. The G′-peak and D-peak shifted linearly with negative gate voltages to higher wavenumbers. Using the G′-peak shift, the charge carrier distribution in an operating FET was mapped at different gate and source-drain voltages with high spatial resolution ( 300 nm) and over large areas. With this simple technique, we were able to visualize directly how the assignment of source and drain electrodes determined channel pinch-off and the onset of the saturation regime in FETs with nonuniform carbon nanotube distributions along the channel. In situ Raman mapping could also be applied to other semiconductors that show significant changes in their Raman spectra with doping.
EAM Import::2019-03-13

Mapping Charge-Carrier Density across the p-n Junction in Ambipolar Carbon-Nanotube Networks by Raman Microscopy - Grimm, Stefan; Jakubka, Florian; Schießl, Stefan; Gannott, Florentina; Zaumseil, Jana (Advanced Materials, 2014)
In situ confocal Raman microscopy is used to map the recombination zone (induced p-n junction) in an ambipolar carbon-nanotube-network transistor with high spatial resolution. The shift of the 2D mode (G' mode) depending on hole and electron accumulation serves as a measure for the local charge-carrier density and provides complementary information about charge transport and recombination in ambipolar transistors.
EAM Import::2019-03-12

Mapping charge transport by electroluminescence in chirality-selected carbon nanotube networks - Jakubka, Florian; Backes, Claudia; Gannott, Florentina; Mundloch, Udo; Hauke, Frank; Hirsch, Andreas; Zaumseil, Jana (Acs Nano, 2013)
We demonstrate random network single-walled carbon nanotube (SWNT) field-effect transistors (FETs) in bottom contact/top gate geometry with only five different semiconducting nanotube species that were selected by dispersion with poly(9,9-dioctylfluorene) in toluene. These FETs are highly ambipolar with balanced hole and electron mobilities and emit near-infrared light with narrow peak widths (<40 meV) and good efficiency. We spatially resolve the electroluminescence from the channel region during a gate voltage sweep and can thus trace charge transport paths through the SWNT thin film. A shift of emission intensity to large diameter nanotubes and gate-voltage-dependent photoluminescence quenching of the different nanotube species indicates excitation transfer within the network and preferential charge accumulation on small band gap nanotubes. Apart from applications as near-infrared emitters with selectable emission wavelengths and narrow line widths, these devices will help to understand and model charge transport in realistic carbon nanotube networks. © 2013 American Chemical Society.

On-Demand Coupling of Electrically Generated Excitons with Surface Plasmons via Voltage-Controlled Emission Zone Position - Zakharko, Yuriy; Held, Martin; Sadafi, Fabrizio-Zagros; Gannott, Florentina; Mandavi, Ali; Peschel, Ulf; Klupp Taylor, Robin; Zaumseil, Jana (ACS Photonics, 2016)
The ability to confine and manipulate light below the diffraction limit is a major goal of future multifunctional optoelectronic/plasmonic systems. Here, we demonstrate the design and realization of a tunable and localized electrical source of excitons coupled to surface plasmons based on a polymer light emitting field-effect transistor (LEFET). Gold nanorods that are integrated into the channel support localized surface plasmons and serve as nanoantennas for enhanced electroluminescence. By precise spatial control of the near-infrared emission zone in the LEFET via the applied voltages the near-field coupling between electrically generated excitons and the nanorods can be turned on or off as visualized by a change of electroluminescence intensity. Numerical calculations and spectroscopic measurements corroborate significant local electroluminescence enhancement due to the high local density of photonic states in the vicinity of the gold nanorods. Importantly, the integration of plasmonic nanostructures hardly influences the electrical performance of the LEFETs, thus, highlighting their mutual compatibility in novel active plasmonic devices.
Keywords: surface plasmon polariton; organic semiconductor; field-effect transistor; electroluminescence; Purcell effect; active plasmonics

Polymer/metal oxide hybrid dielectrics for low voltage field-effect transistors with solution-processed, high-mobility semiconductors - Held, Martin; Schießl, Stefan; Miehler, Dominik; Gannott, Florentina; Zaumseil, Jana (Applied Physics Letters, 2015)
Transistors for future flexible organic light-emitting diode (OLED) display backplanes should operate at low voltages and be able to sustain high currents over long times without degradation. Hence, high capacitance dielectrics with low surface trap densities are required that are compatible with solution-processable high-mobility semiconductors. Here, we combine poly(methyl methacrylate) (PMMA) and atomic layer deposition hafnium oxide (HfOx) into a bilayer hybrid dielectric for field-effect transistors with a donor-acceptor polymer (DPPT-TT) or single-walled carbon nanotubes (SWNTs) as the semiconductor and demonstrate substantially improved device performances for both. The ultra-thin PMMA layer ensures a low density of trap states at the semiconductor-dielectric interface while the metal oxide layer provides high capacitance, low gate leakage and superior barrier properties. Transistors with these thin (łeq70 nm), high capacitance (100–300 nF/cm2) hybrid dielectrics enable low operating voltages (<5 V), balanced charge carrier mobilities and low threshold voltages. Moreover, the hybrid layers substantially improve the bias stress stability of the transistors compared to those with pure PMMA and HfOx dielectrics.
EAM Import::2019-03-08

Self-Assembled Monolayer Dielectrics for Low-Voltage Carbon Nanotube Transistors with Controlled Network Density - Schießl, Stefan; Gannott, Florentina; Etschel, Sebastian; Schweiger, Manuel; Grünler, Saeideh; Halik, Marcus; Zaumseil, Jana (Advanced Materials Interfaces, 2016)

Spray-coatable ionogels based on silane-ionic liquids for low voltage, flexible, electrolyte-gated organic transistors - Thiemann, Stefan; Sachnov, Swetlana; Gruber, Mathias; Gannott, Florentina; Spallek, Stefanie; Schweiger, Manuel; Krückel, Johannes; Kaschta, Joachim; Spiecker, Erdmann; Wasserscheid, Peter; Zaumseil, Jana (Journal of Materials Chemistry C, 2014)
We introduce a new type of silane-based ionogels that are produced by gelation of the ionic liquid 3-methyl-1-(3-(triethoxysilyl)propyl)-imidazolium bis(trifluoromethylsulfonyl)imide ([(EtO)3SiPMIM][TFSI]) with tetramethylorthosilane and formic acid. In the obtained ionogels the cations are involved in the network formation while the anions can move freely. The ionogels show advantageous properties for application in flexible electronics, such as low modulus, solution processability and high specific capacitance. Spray-coated ionogels were used as high capacitance gate dielectrics for organic (poly[3-hexylthiophene], P3HT) electrolyte-gated transistors (EGTs) that operated at very low voltages (<2 V) with high on/off ratios in air over weeks. Devices fabricated on polymer foil remained functional during repeated bending cycles with strains up to 2.3%.

Trion Electroluminescence from Semiconducting Carbon Nanotubes - Jakubka, Florian; Grimm, Stefan; Zakharko, Yuriy; Gannott, Florentina; Zaumseil, Jana (ACS nano, 2014)
Near-infrared emission from semiconducting single-walled carbon nanotubes (SWNTs) usually results from radiative relaxation of excitons. By binding an additional electron or hole through chemical or electrochemical doping, charged three-body excitons, so-called trions, are created that emit light at lower energies. The energy difference is large enough to observe weak trion photoluminescence from doped SWNTs even at room temperature. Here, we demonstrate strong trion electroluminescence from electrolyte-gated, light-emitting SWNT transistors with three different polymer-sorted carbon nanotube species, namely, (6,5), (7,5) and (10,5). The red-shifted trion emission is equal to or even stronger than the exciton emission, which is attributed to the high charge carrier density in the transistor channel. The possibility of trions as a radiative relaxation pathway for triplets and dark excitons that are formed in large numbers by electron-hole recombination is discussed. The ratio of trion to exciton emission can be tuned by the applied voltages, enabling voltage-controlled near-infrared light sources with narrow line widths that are solution-processable and operate at low voltages (<3 V).
EAM Import::2019-03-13

ZA-derived phonons in the Raman spectra of single-walled carbon nanotubes - Vierck, Asmus; Gannott, Florentina; Schweiger, Manuel; Zaumseil, Jana; Maultzsch, Janina (Carbon, 2017)
We report the observation of four Raman modes in individual, aligned single-walled carbon nanotubes, with frequencies between the RBM and D modes, and above the G(+/-) modes. By studying the diameter and excitation-energy dependence, we find that these strongly dispersive and comparatively intense modes share the lowest-frequency helical phonon branch as the origin, which can be derived from the out-of plane acoustic (ZA) phonon branch of graphene. This ZA phonon is observed due to a defect-assisted, double-resonant process, similar to the D mode; its two-phonon overtones and combinations with transverse optical (TO) phonons do not require defects. Our assignment is supported by a theoretical model based on sixth-nearest neighbour tight-binding and a force-constant approach. We present a complete theoretical evaluation of the diameter and excitation-energy dependence of the ZA, 2ZA, and TO +/- ZA modes, which fits very well to our experimental results and previous studies of the so-called region of intermediate frequency modes. (C) 2017 Elsevier Ltd. All rights reserved.